Comparison of capillary electrophoregram among heterozygous Hb Hope, Hb Hope/α-thalassemia-1 SEA type deletion and Hb Hope/β0- thalassemia - Pornprasert S. (2017)
Background: Hemoglobin (Hb) A 2 is artifactually elevated in cases of heterozygous Hb Hope when measured by capillary electrophoresis (CE). However, there is no report of HbA 2 levels and capillary electrophoregrams for associa-tions of heterozygote of Hb Hope with α-thalassemia nor β-thalassemia. Methods: Levels of HbA 0 , HbA 2 and Hb Hope in 16 heterozygous Hb Hope, 3 Hb Hope/a-thalassemia-1 SEA type deletion and 2 Hb Hope/β 0 - thalassemia were measured by CE. Electrophoregram and the levels of those were compared within these three groups. Results: Artifactually elevated HbA 2 levels (≥4%) were found in both groups of heterozygous Hb Hope and Hb Hope/α-thalassemia-1 SEA type deletion. Manual corrections were performed by adjusting baselines, and results showed that means of HbA 2 in both groups decreased from 4.47 % and 4.03 % to 1.93 % and 1.77 %, respectively. The highest levels of HbA 2 and Hb Hope were observed in samples with Hb Hope/α 0 -thalassemia. Moreover, HbA 0 was not observe in these cases. Conclusions: The elevation of HbA 2 in patients with heterozygous Hb Hope and with Hb Hope/α-thalassemia-1 SEA type deletion measured by CE leads to incorrect β-thalassemia trait diagnosis. However, using CE electrophoregram together with levels of HbA 0 , HbA 2 and Hb Hope would be a more accurate and precise method for diagnosis of Hb Hope/βdeg;-thalassemia. © 2012 by Walter de Gruyter. Berlin. Boston.